Delivery of psychiatric care to those mentally ill in Ireland - proposals for change - Walsh, Dermot (Statistical and Social Inquiry Society of Ireland, 1988)
A working group was set up by the Minister for Health, Mrs Eileen Desmond TD in October 1981 "to examine the main components, both institutional and community, of the psychiatric services, to assess the existing services, to clarify their objectives and to draw up planning guidelines for future development of the service with due regard to cost implications, to carry out such studies and to take part in such consultations as are necessary to assist this examination". In December 1984 the group's report entitled "Psychiatric Services - Planning for the Future" was presented to the Minister for Health, Barry Desmond TD. It will be the purpose of this paper briefly to describe the historical background leading to the setting up of the study group and to synthesise its main recommendations and the constraints on their implementation.
Read before the Society, 25 February, 1988
Keywords: Psychiatric care; Health provision; 314.15